AIS and Decision-Making - Markus Granlund; Henri Teittinen (Routledge, 2022)
Decision making plays an important role in the daily life of managers at different organizational levels. In order to be able to make justified decisions, managers need contextually relevant information to build their decisions on. In this Chapter, we outline how modern accounting information systems (AIS) can support managerial decision making in contemporary organizations. We first describe how the decision making and data environments frame decision making situations. After that we apply the Burchell et al. (1980) framework to analyse in more detail how AIS can support managers in particular decision making situations.
The Routledge Companion to Accounting Information Systems